Strengthening the Integration of Rural and Agricultural Development: The Case of Bali Province, Indonesia - Sagar, Deepika (Journal of Social Science and Humanities, 2025)
Presently, the agricultural sector has great role in supporting and accelerating economic development in the developing countries. Development of agriculture is always related to rural development since it is an integral part to rural economic development. Therefore, agricultural and rural development should be designed to increase the productivity of land, crops, and human resources in order to improve the welfare of rural village. The implementation of agricultural and rural development should be done by involving the rural institutions. Several problems have still been found in the agricultural and rural development that should be properly managed by considering various aspects. In Bali Province, the implementation of agricultural and rural development can be conducted to develop tourism, industry, environment, and other economic activities. The agro - tourism, agro - industry, integrated farming system (system of crops and livestock) and village - owned enterprises could be developed as a response of the rural development.